Social media, youths and political participation in Malaysia: a review of literature - Abdullah, Nor Hafizah; Hassan, Isyaku; Ahmad, Muhamad Fazil; Hassan, Nor Azlili; Ismail, Mohd Mahadee (Human Resource Management Academic Research Society, 2021)
In today’s modern world, political knowledge is not only conveyed or sought through traditional methods such as political rallies but also via social media such as Facebook, YouTube and Twitter. The search for political information through social media has now become a global phenomenon. In recent years, the use of social media among youths in Malaysia has increased significantly. It is, thus, prudent to explore the use of social media platforms amongst youths in Malaysian. Therefore, this paper offers a review of studies on youth participation in politics via social media, particularly in the Malaysian context. The paper provides an overview of how Malaysian youths seek political information through social media and reviews recent information related to online resources in the political context. It was envisaged that this paper could advance our understanding of the trend and level of youth participation in politics via social media, particularly in Malaysia. Additionally, this review could provide useful information on the online dissemination and consumption of political information.